A multispacecraft event study of Pc5 ultralow‐frequency waves in the magnetosphere and their external drivers. Issue 5 (9th May 2017) - Wang, Chih‐Ping; Thorne, Richard; Liu, Terry Z.; Hartinger, Michael D.; Nagai, Tsugunobu; Angelopoulos, Vassilis; Wygant, John R.; Breneman, Aaron; Kletzing, Craig; Reeves, Geoffrey D.; Claudepierre, Seth G.; Spence, Harlan E.
Abstract: We investigate a quiet time event of magnetospheric Pc5 ultralow‐frequency (ULF) waves and their likely external drivers using multiple spacecraft observations. Enhancements of electric and magnetic field perturbations in two narrow frequency bands, 1.5–2 mHz and 3.5–4 mHz, were observed over a large radial distance range from r  ~ 5 to 11  R E . During the first half of this event, perturbations were mainly observed in the transverse components and only in the 3.5–4 mHz band. In comparison, enhancements were stronger during the second half in both transverse and compressional components and in both frequency bands. No indication of field line resonances was found for these magnetic field perturbations. Perturbations in these two bands were also observed in the magnetosheath, but not in the solar wind dynamic pressure perturbations. For the first interval, good correlations between the flow perturbations in the magnetosphere and magnetosheath and an indirect signature for Kelvin‐Helmholtz (K‐H) vortices suggest K‐H surface waves as the driver. For the second interval, good correlations are found between the magnetosheath dynamic pressure perturbations, magnetopause deformation, and magnetospheric waves, all in good correspondence to interplanetary magnetic field (IMF) discontinuities. The characteristics of these perturbations can be explained by being driven by foreshock perturbations resulting from these IMF discontinuities. This event shows that even during quiet periods, K‐H‐unstable magnetopause and ion foreshock perturbations can combine to create a highly dynamic magnetospheric ULF wave environment. Key Points: Enhanced magnetospheric Pc5 ULF waves driven by magnetopause disturbances during northward IMF Waves driven by Kelvin‐Helmholtz flow vortices Waves driven by foreshock perturbations resulting from IMF discontinuities